(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In current world scenario organic farming is a famous agricultural practice and covering a total area of approximately 71.5 Mha worldwide. Due to the involvement of certain practices in organic farming, food safety and human health is threatened by the flows of various environmental pollutants.